Level of knowledge (% correct answers). - Manja D. Jensen (11592448) (2025)
Note: The table shows the level of knowledge at the four poll inquiry time points expressed as % correct answers to the 13 knowledge items. T1 = inquiry time point 1 (recruitment), T2 = inquiry time point 2 (after video information), T3 = inquiry time point 3 (after deliberation), T4 = inquiry time point 4 (one month after the citizens’ assembly). (TIFF)